1997
DOI: 10.1046/j.1365-3059.1997.d01-23.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leaf rust (Puccinia hordei) on yield response in barley (Hordeum vulgare L.) crops with different yield potentials

Abstract: The effect of leaf rust was investigated on field-grown crops, in two consecutive seasons, each at a single location, using a non-replicated design. The experiments involved three crops and 10 distinct epidemics in the 1987/8 season, and four crops with seven epidemics in the 1988/9 season. The epidemics were concurrent in each season in subplots within each crop, and the yield range was from 2 . 2-9 . 0 t ha ¹1 in nil-diseased plots. Variation in the experiments, assessed as the percentage coefficient of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Data of Whelan et al (1997), who observed yield losses due to leaf rust of up to 63%, underline the tremendous damage potential of leaf rust. In comparison, net blotch has been observed to cause up to about 34% yield loss in barley, depending on the variety (Khan 1987a, b).…”
Section: Model Frameworkmentioning
confidence: 96%
“…Data of Whelan et al (1997), who observed yield losses due to leaf rust of up to 63%, underline the tremendous damage potential of leaf rust. In comparison, net blotch has been observed to cause up to about 34% yield loss in barley, depending on the variety (Khan 1987a, b).…”
Section: Model Frameworkmentioning
confidence: 96%
“…Moreover, the extent of the imbalance differed widely between sites and years (Bingham et al , 2007 a ). Foliar disease is known to reduce both the number of grains per m 2 and the average grain weight, depending on the timing of the epidemic (Wright & Gaunt, 1992; Conry & Dunne, 1993; Whelan et al , 1997), and preliminary findings from ongoing research suggest that the effects on average grain weight are the result of restrictions on potential grain size (unpublished data). Thus, both components of grain sink capacity can be reduced by disease.…”
Section: Source–sink Balance and Stem Reservesmentioning
confidence: 99%
“…low grain numbers) would be relatively more tolerant of post‐anthesis disease than those with small reserves and high potential. However, no association was found between the yield potential of spring barley and its yield response to leaf rust (Whelan et al , 1997). The failure to establish such a relationship may be because disease reduced grain sink capacity more than post‐anthesis photosynthate availability in crops of both high and low yield potential.…”
Section: Source–sink Balance and Stem Reservesmentioning
confidence: 99%
“…In spring barley, disease reduced the amount of storage reserves deposited, but increased the proportion subsequently used for grain fi lling (Gaunt & Wright, 1992). However, contrary to the hypothesis that crops with large storage reserves and low yield potential (small grain number) would be more tolerant of disease (Gaunt & Wright, 1992), no relationship was found between yield potential and yield loss caused by leaf rust (Whelan et al, 1997).…”
Section: Source-sink Relations and Storage Reserves 754mentioning
confidence: 94%